Simulation and Experimental Verification of Barrel Finishing of Spiral Bevel Gears Based on the DEM - Yang Shufeng; Gao Yang; Wang Feng; Li Zhisheng; Yu Wentao; Xu Wenbo (Jixie chuandong)
The tooth surface of spiral bevel gears is a spatial curved surface, and the change of tooth surface roughness can have a significant impact on its meshing performance, directly affecting the vibration, bearing and other performance of the system. A theoretical simulation and an experimental research of an aviation spiral bevel gear is carried out using the parallel spindle type barrel finishing process, a mathematical model of the process motion is established, the formula of cutting speed between abrasive and tooth surface is deduced, and the main factors affecting the result are analyzed; with the help of the Hertz-Mindlin with archard wear model of the EDEM software, the tooth surface wear is simulated; through this process, the surface quality of the disc spiral bevel gear surface is experimentally studied. The results show that using this process, the burr of the gear surface can be eliminated, the corner is rounded, the Ra of gear surface is reduced from 0.8 μm to about 0.4 μm, and the tooth surface morphology tends to be isotropic, which lays a foundation for further research of gear contact performance and industrial application.